Coupling of Cell Surface Biotinylation and SILAC-Based Quantitative Proteomics Identified Myoferlin as a Potential Therapeutic Target for Nasopharyngeal Carcinoma Metastasis - Li, Maoyu; Peng, Fang; Wang, Guoqiang; Liang, Xujun; Shao, Meiying; Chen, Zhuchu; Chen, Yongheng (Frontiers in Cell and Developmental Biology, 2021)
Distant metastasis is a major cause of treatment failure in nasopharyngeal carcinoma (NPC) patients. Cell surface proteins represent attractive targets for cancer diagnosis or therapy. However, the cell surface proteins associated with NPC metastasis are poorly understood. To identify potential therapeutic targets for NPC metastasis, we isolated cell surface proteins from two isogenic NPC cell lines, 6-10B (low metastatic) and 5-8F (highly metastatic), through cell surface biotinylation. Stable isotope labeling by amino acids in cell culture (SILAC) based proteomics was applied to comprehensively characterize the cell surface proteins related with the metastatic phenotype. We identified 294 differentially expressed cell surface proteins, including the most upregulated protein myoferlin (MYOF), two receptor tyrosine kinases(RTKs) epidermal growth factor receptor (EGFR) and ephrin type-A receptor 2 (EPHA2) and several integrin family molecules. These differentially expressed proteins are enriched in multiple biological pathways such as the FAK-PI3K-mTOR pathway, focal adhesions, and integrin-mediated cell adhesion. The knockdown of MYOF effectively suppresses the proliferation, migration and invasion of NPC cells. Immunohistochemistry analysis also showed that MYOF is associated with NPC metastasis. We experimentally confirmed, for the first time, that MYOF can interact with EGFR and EPHA2. Moreover, MYOF knockdown could influence not only EGFR activity and its downstream epithelial–mesenchymal transition (EMT), but also EPHA2 ligand-independent activity. These findings suggest that MYOF might be an attractive potential therapeutic target that has double effects of simultaneously influencing EGFR and EPHA2 signaling pathway. In conclusion, this is the first study to profile the cell surface proteins associated with NPC metastasis and provide valuable resource for future researches.